principles of paleontology - Raup, David M; Stanley, Steven M (New Delhi : CBS, 1985)
Reading books is a kind of enjoyment. Reading books is a good habit. We bring you a different kinds of books. You can carry this book where ever you want. It is easy to carry. It can be an ideal gift to yourself and to your loved ones. Care instruction keep away from fire.
Bibliography 449-465p.; Author index 469-472p.; Subject index 473-481p.; Reprint 2004
Keywords: Cladistic taxonomy; Fossil populations; Marine ecosystem; Ontogenetic variation